2020
DOI: 10.3390/ani10122291
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Tall Fescue Seed Reduces Ewe Milk Production, Lamb Birth Weight and Pre-Weaning Growth Rate

Abstract: Endophyte-infected tall fescue (E+) produces ergovaline and ergovalinine, which are mycotoxins that act as dopamine agonists to suppress prolactin and induce vasoconstriction. The experiment was designed as a 3 × 2 × 2 factorial with DRD2 genotype (AA, AG, GG), fescue seed (endophyte-free, E− or endophyte-infected, E+), stage of gestation (MID, d (day) 35–85; LATE, d 86–parturition) and all interactions in the model. Pregnant Suffolk ewes (n = 60) were stratified by genotype and fed E+ or E− seed in a total mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…38,47 Previous research found that exposure to E+ fescue during late gestation reduced fetal BW at gd133 by 15% 11 and birth weight by 10.2%. 31 Brain to fetal body weight was increased with exposure to mycotoxins in this study, which is an indicator of asymmetrical growth and IUGR. [15][16][17] This agrees with our earlier work that showed asymmetrical growth in lambs at gd133 10 after exposure to mycotoxins during late gestation that altered growth of the offspring and delayed puberty in females.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…38,47 Previous research found that exposure to E+ fescue during late gestation reduced fetal BW at gd133 by 15% 11 and birth weight by 10.2%. 31 Brain to fetal body weight was increased with exposure to mycotoxins in this study, which is an indicator of asymmetrical growth and IUGR. [15][16][17] This agrees with our earlier work that showed asymmetrical growth in lambs at gd133 10 after exposure to mycotoxins during late gestation that altered growth of the offspring and delayed puberty in females.…”
Section: Discussionsupporting
confidence: 50%
“…Reductions in serum prolactin levels are commonly reported in sheep grazing endophyte-infected tall fescue pastures [33][34][35] or fed E+ tall fescue seed containing ergot alkaloids. 11,31,36 The reductions in prolactin concentrations are caused by the structural similarity of the ergoline ring of ergot alkaloids to dopamine, which allows them to interact with D2 dopamine receptors. 7 During late gestation, placenta growth plateaus around gd80 37 to gd90 38 and then remodeling of the placenta occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, others have also reported no change in calf birth weight when cows grazed E+ fescue prior to calving [ 19 , 48 , 49 ]. In contrast, others have shown that calves or lambs born to dams exposed to endophyte-infected tall fescue during gestation have reduced birthweights by 5% [ 18 ], 15% [ 50 , 51 ] or 36% [ 52 ]. Britt et al [ 50 ] found that exposure to ergot alkaloids during late gestation had the greatest impact on fetal development with little to no effect when fed during mid-gestation in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Calf gains during this first 30 days period were lower for E+ than NOV. Feeding toxic endophyte-infected seed to ewes during mid and late gestation reduced milk production by 59 to 82% and reduced pre-weaning growth rates [ 51 ], which altered subsequent puberty development and post-natal growth [ 64 ]. In addition, cow calving rate was lower in cows that grazed E+ fescue during late gestation and early lactation.…”
Section: Discussionmentioning
confidence: 99%